The Integrated Development of Aesthetic Education and Rural Economy in the Context of Rural Revitalization: A Case Study of Jieshou City, Anhui Province - Zhao, Jing (International Journal of Global Economics and Management, 2025)
Based on the rural revitalization strategy, by leveraging the advantages of Anhui University of Finance and Economics, a public welfare activity titled "The Integrated Development of Aesthetic Education and Rural Economy in the Context of Rural Revitalization: A Case Study of Jieshou City, Anhui Province" was carried out in rural areas. The project team members conducted in-depth investigations and research on the current situation of rural aesthetic education [1], analyzed the reasons, and provided solutions. They continuously explored rural aesthetic education to provide channels for rural children to access knowledge of beauty and broaden their horizons. By entering the campus for investigation and providing various aesthetic education activities, the team members not only understood the current situation of aesthetic education knowledge in the local area but also enriched the extracurricular lives of rural children, further promoting rural cultural revitalization and prosperity. The implementation of this project has helped us to better understand the shortage of rural aesthetic education resources and the lack of teaching staff, which is conducive to constructing the basic framework of rural aesthetic education development, promoting rural economic development, and more precisely promoting rural cultural revitalization.